Inequality and Welfare Evaluation of Heterogeneous Income Distributions - Anthony Shorrocks (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This paper establishes the principles which should govern the welfare and inequality analysis of heterogeneous income distributions. Two basic criteria - the 'equity preference' condition and the 'compensation principle' - are shown to be fundamentally incompatible. The paper favours the latter, thereby vindicating the traditional method of dealing with heterogeneous samples. However, inequality and welfare comparisons will usually be well defined only if equivalent incomes are obtained using constant scale factors; and researchers will need to distinguish clearly between inequality of nominal incomes and inequality of living standards. Furthermore, household observations must always be weighted according to family size.
Keywords: 330; income distribution; inequality; living standards; needs